Evaluation of fennel (Foeniculum vulgare Mill.) germplasm for production and quality - Rajput, Sanjeev Agrawal, Dhirendra Singh, S S (Journal of Spices and Aromatic Crops, 2003)
Seventy four fennel (Foeniculum vulgare Mill.) accessions along with check varieties RF-101 and RF-125 were evaluated for yield and yield attributing characters. Eight promising accessions for seed yileld were then evaluated for volatile oil content. The oil content of three most promising acceSSIOns along with check varieties were analyzed on a CLC. The accession, UF-178, exhibited superiority over other accessions in respect of yield attributing characters such as branches plant-1, seeds umbel-1 and seed yield. UF-177 was found to be superior with respect to volatile oil content as well as volatile oil yield. UF-177 has the least fenchone content among the three. UF-179 was having maximum anethole content, which was found to be at par with variety RF-101. These three accessions may be exploited in breeding programmes for production and quality.